Implementation Of The Contract System And Employee Welfare PKWT (Specified Time Work Agreement) At PT Jasamarga Jogja Solo - Ardina Nurresti; Andriyastuti Suratman (International Journal of Economics, Business and Innovation Research, 2024)
The research object of this study is the issue of the contract system and the welfare of PKWT, or contract employees. I chose this study because I see that there are still many companies that use contract employees to save on operational costs, which results in losses for the contract employees themselves. The results of the research show that the contract employees are satisfied with the welfare of the PKWT.